STUDIES ON DELAYED HYPERSENSITIVITY : I. INFERENCES ON THE COMPARATIVE BINDING AFFINITIES OF ANTIBODIES MEDIATING DELAYED AND IMMEDIATE HYPERSENSITIVITY REACTIONS IN THE GUINEA PIG - Levine, Bernard B. (The Rockefeller University Press, 1965)
Experiments carried out with several well defined antigenic systems (hapten conjugates of poly-L-lysine and guinea pig serum albumin) in guinea pigs demonstrated that: 1. Arthus reactions also manifest carrier specificity, although to a smaller extent than do delayed hypersensitivity reactions. 2. Desensitization by injection of minute doses of antigen results in moderate specific desensitization of delayed hypersensitivity without desensitization of Arthus reactivity to the same antigenic determinant. 3. Insoluble antigen-antibody complexes prepared from high affinity guinea pig antibodies can elicit specific delayed skin reactions in sensitized guinea pigs. 4. Homologous conjugates of structurally similar haptens show considerably less cross-reactivity in delayed reactions than in immediate hypersensitivity reactions to the same antigenic determinant. These experimental results are interpreted as indicating that delayed hypersensitivity reactions in the guinea pig are mediated by "antibodies" of comparatively high binding affinities. High binding affinities are achieved for these antibodies more likely by closer structural adaptation between antigen and antibody than by a larger area of specific contact.